Sarcoma-like mural nodule in a borderline mucinous tumor of the ovary: A rare entity - Prithwijit Ghosh; Kaushik Saha; Sourav Bhowmik (Wolters Kluwer Medknow Publications, 2014)
Sarcoma-like mural nodule (SLMN) is a very uncommon and misleading benign entity which may be associated with benign, borderline or malignant mucinous neoplasm of the ovary. It should be distinguished from other malignant mural nodules with sarcoma, carcinosarcoma or anaplastic carcinoma for proper management. We report a rare case of SLMN in a borderline mucinous tumor of the ovary in a 30-year-old lady. In spite of having confusing histopathological features the final diagnosis was made depending on the younger age of the patient, well circumscription of the nodule, absence of vascular invasion and immunohistochemical profile.